2017
DOI: 10.3390/catal7040108
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Hydrolysis of Lignocellulose by Acidic Ionic Liquids under Low-Toxic Condition to Microorganisms

Abstract: Abstract:Lignocellulose is known as a renewable resource, and acidic ionic liquids have been highlighted as efficient catalysts for hydrolysis of cellulose. To achieve successive hydrolysis and fermentation, efficient hydrolysis with sufficiently diluted acidic ionic liquids is necessary because acidic ionic liquids are toxic to fermentative microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Takahashi et al found that a 0.05 M 1-(1-butylsulfonic)-3-methylimidazolium hydrogen sulfate ([Sbmim][HSO 4 ]) solution was sufficiently low to allow for the growth of E. coli. In the diluted ILs, glucose yield of 48% was obtained from the hydrolysis of bagasse at 190 C (Kuroda et al, 2017). The efficient isolation of generated reducing sugar in ILs and the compatibility between microorganism and ILs remain to be fully investigated.…”
Section: Hydrolysis Of Cellulose In Ilsmentioning
confidence: 99%
“…Takahashi et al found that a 0.05 M 1-(1-butylsulfonic)-3-methylimidazolium hydrogen sulfate ([Sbmim][HSO 4 ]) solution was sufficiently low to allow for the growth of E. coli. In the diluted ILs, glucose yield of 48% was obtained from the hydrolysis of bagasse at 190 C (Kuroda et al, 2017). The efficient isolation of generated reducing sugar in ILs and the compatibility between microorganism and ILs remain to be fully investigated.…”
Section: Hydrolysis Of Cellulose In Ilsmentioning
confidence: 99%
“…Because these ILs are capable of dissolving cellulose under mild conditions, they allow for improvement of energy efficiency in cellulose processing. Recently, it was reported that one can extract glucose from lignocellulose in IL solutions by using a hydrolysis reaction. , It indicates that ILs are promising solvents for biomass processing of cellulose. In addition, fabrication of polysaccharide ion gel and films using ILs has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that one can extract glucose from lignocellulose in IL solutions by using a hydrolysis reaction. 11,12 It indicates that ILs are promising solvents for biomass processing of cellulose. In addition, fabrication of polysaccharide ion gel and films using ILs has been reported.…”
Section: ■ Introductionmentioning
confidence: 99%